Effects of Tillage and Crop Establishment Methods, Crop Residues, and Nitrogen Levels on Wheat Productivity, Energy-savings and Greenhouse Gas Emission under Rice -Wheat Cropping System - Sah, G.; Shah, S. C.; Sah, S. K.; Thapa, R. B.; McDonald, A.; Sidhu, H. S.; Gupta, R. K.; Tripathi, B. P.; Justice, S. E. (Nepal Journal of Science and Technology, 2015)
Field experiments were conducted to evaluate conventional tillage (CT), permanent raised bed (PRB), and zero tillage (ZT) with residue retention and removal at three nitrogen levels (0, 100, and 120 kg N ha-1) on wheat productivity, energy input and energy output, energy use efficiency, specific energy, and CO2 emission from 2010 to 2012 under rice-wheat system at Pheta V.D.C, Bara, Nepal. The experiments were carried out in strip split plot designs with three replications. Zero tillage wheat produced significantly higher grain yield (2616.5 kg ha-1), saved 10.4 % energy input, increased energy output (12.4 %), enhancing energy use efficiency by 25.2 % and reducing specific energy by 23.6 %, as compared to conventional tillage. Diesel consumption on crop establishment and irrigations were the lowest for ZT (48.6 liter ha-1) and the highest for CT (86.3 liter ha-1). PRB consumed the lowest quantity of diesel on two irrigations (34.6 liter ha-1) with higher energy use efficiency (3.4 %) and lower specific energy (8.76 MJ kg-1) over CT. The CO2 emission from CT was the highest (224.32 kg ha-1) over ZT (126.4 kg ha-1) and PRB (146.11 kg ha-1). Residue retention increased 4 % grain yield over residue removal. Without nitrogen application, energy output was the lowest (34192 MJ ha-1) with the highest specific energy (12.6 MJ kg-1). Thus, zero-till wheat with 40-cm residue retention and 100 kg N ha-1 application was suggested for mass scale adoption in the Tarai region of Nepal. DOI: http://dx.doi.org/njst.v15i2.12104 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 1-10